2020
DOI: 10.52571/ptq.v17.n34.2020.352_p34_pgs_335_342.pdf
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Processes in the Ai-Ti-Si System Under Thermal Shock

Abstract: In recent years, much attention of developers of integrated microcircuits is given to designing novel types of microprocessors, development, and mastery of technologies of both multilayer 3D integrated circuits and making devices based on complex semiconductors. The aim of the present work is to study thermal processes in the Al-Ti-Si multilayer system up to the development of degradation processes. The degradation issues in aluminum metallization with titanium sublayer deposited onto silicon surface are consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Figure 3 shows the heating dynamics of interconnects on silicon wafers, taking into account the Ti and SiO2 sublayers. The presence of a dielectric film increases the thermal load on the structure; it was found that the formation of straightened areas is associated with poor adhesion and a local decrease in the cross-section of the film [14]. In the case of the Al-Si binary structure, the mechanisms of structure destruction are associated with melting of the metallization track and contact melting at the Al-Si interface.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the heating dynamics of interconnects on silicon wafers, taking into account the Ti and SiO2 sublayers. The presence of a dielectric film increases the thermal load on the structure; it was found that the formation of straightened areas is associated with poor adhesion and a local decrease in the cross-section of the film [14]. In the case of the Al-Si binary structure, the mechanisms of structure destruction are associated with melting of the metallization track and contact melting at the Al-Si interface.…”
Section: Resultsmentioning
confidence: 99%